Primary anaplastic astrocytoma of the brain after prophylactic cranial irradiation in a case of acute lymphoblastic leukemia: Case report and review of the literature - Imtiaz Ahmed; Sapna Krishnamurthy; Aanchal Kakkar; Pramod Kumar Julka; Goura Kishor Rath (Indian Journal of Medical and Paediatric Oncology)
A 6½-year-old boy had developed acute lymphoblastic leukemia and was treated with systemic chemotherapy, intrathecal triple drug regimen and prophylactic cranial irradiation. After 10 years he developed anaplastic astrocytoma of the postero-superior cerebellum on the left side while leukemia was in remission. He was treated with surgical excision, followed by adjuvant three dimensional conformal radiotherapy and is on salvage chemotherapy with temozolamide. It is possible that the anaplastic astrocytoma may be a radiation induced malignancy.